2008
DOI: 10.1038/4551164a
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical futures: A fiendish puzzle

Abstract: Where should the drug industry go to find new ideas? In the first of two features, Alison Abbott asks if the future lies in systems biology -a field that attempts to piece together 'everything'.In the second, David Cyranoski looks at drug companies' attraction to China.Cristiano Migliorini has seen systems biology deliver promising drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The most actively developing screening techniques are high--throughput screening (HTS) (computer simulated molecular targeting based on biochemical pathway), new chemical entities (NCE) (a new therapeutic molecule or compound that has not been tested on humans), and (3DMD) (3D molecular docking), specifically 3D modeling of interacting molecules with a known structure, based on their spacial arrangement [7,8]. However, ever though research in this has made a great progress, at present certain crisis is observed in the methodology of search for new drugs, since computer modeling has failed to justify expectations and investments, and this situation forces pharmaceutical companies to search for new approaches to investing into pharmaceutical industry [9].…”
Section: Biosensor Screening At the Stage Of Drug Developmentmentioning
confidence: 99%
“…The most actively developing screening techniques are high--throughput screening (HTS) (computer simulated molecular targeting based on biochemical pathway), new chemical entities (NCE) (a new therapeutic molecule or compound that has not been tested on humans), and (3DMD) (3D molecular docking), specifically 3D modeling of interacting molecules with a known structure, based on their spacial arrangement [7,8]. However, ever though research in this has made a great progress, at present certain crisis is observed in the methodology of search for new drugs, since computer modeling has failed to justify expectations and investments, and this situation forces pharmaceutical companies to search for new approaches to investing into pharmaceutical industry [9].…”
Section: Biosensor Screening At the Stage Of Drug Developmentmentioning
confidence: 99%